ONLINE INFORMATION WEB APPLICATIONS CLINIC SARASWATI USING PHP, DREAMWEAVER AND MYSQL - Agus Priyaji; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2010)
In modern times, the rapid development of world information. This continues to befelt when it appears in Internet services, which obviously makes it easy to fellowInternet users to exchange data. If before, the Information and Communicationsconducted a simple, currently people can use technology more effectively andefficiently. The application website is very useful in providing information servicesalso explained that existed at the clinic Saraswati because of the media websites canbe accessed at various circles with a fairly sophisticated system like this now.Saraswati Clinic Website page views are presented on the website that is easilyunderstood by consumers / patient in obtaining information from the main menu tosearch for other information.